Assessing the Failure of International Mediation in the Nagorno-Karabakh Conflict: Legal Positivism, Conflict Transformation and the limits of State Sovereignty - Maqsood, Asia; Jamil, Muhammad Shoaib; Warraich, Aisha (Annals of Human and Social Sciences, 2025)
Why has international mediation, in particular by the OSCE Minsk Group, failed to resolve the Nagorno-Karabakh conflict is the subject of the study. Longstanding ethnic disputes and historical territorial claims generally have sparked the conflict, which previously had escalated several times in spite of numerous ceasefires and peace initiatives. The study reviews, in a conceptual and qualitative approach, the mediations dynamics by synthesizing legal positivism, instrumentalist theory and frameworks of conflict transformation. An analysis indicates that strong precluding of state sovereignty, lack of conflict transforming devices, and geopolitical rivalries prevented mediation attempts and created ground for Azerbaijan’s coercive occupation. To prevent further escalations, it is a requirement to integrate robust legal enforcement with grassroots reconciliation, third party accountability, and inclusive peacebuilding in order to address underlying grievances. Transformative, inclusive mediation strategies should take precedence over normative legal strategies because the mediation strategies have to fit in with the complexities of ethnic conflict and not vice versa. The study suggests reforms for a lasting peace in general.